Post Operative Hyperbilirubinemia after Cardiac Surgery: A Cross-Sectional Study in National Institute of Cardiovascular Diseases, Karachi - Ahmad, Hamad; Bilal Awan, Muhammad Asad; Hassan, Ikram; Khan, Muhammad Ishaq; Iqbal, Izaz; Zada, Shakir (Indus Journal of Bioscience Research, 2025)
Background: Postoperative hyperbilirubinemia is a frequent and clinically significant complication following cardiac surgery, with reported incidence ranging from 10% to 40%. It has been associated with increased postoperative morbidity, prolonged ICU stay, low-output syndrome, renal dysfunction, and higher mortality. Despite advances in cardiopulmonary bypass techniques and perioperative care, hyperbilirubinemia remains prevalent and understudied, particularly in local populations. Objective: To determine the frequency of postoperative hyperbilirubinemia in patients undergoing adult cardiac surgery. Methods: A descriptive cross-sectional study was conducted at the Department of Cardiac Surgery, National Institute of Cardiovascular Diseases (NICVD), Karachi from 17 Feb 2025 to 17 May 2025. A total of 289 adult patients undergoing cardiac surgery were enrolled using non-probability consecutive sampling. Patients with preoperative hyperbilirubinemia, liver disease, or heart failure were excluded. Serum bilirubin levels were monitored during the hospital stay, and hyperbilirubinemia was defined as total bilirubin >2.0 mg/dL. Results: Out of 289 patients who underwent cardiac surgery, 76 (26.3%) developed postoperative hyperbilirubinemia. These patients were older (59.2 vs. 55.8 years, p = 0.01), had a higher prevalence of diabetes (58% vs. 36%, p = 0.002), and experienced longer bypass times (98.2 vs. 89.5 minutes, p = 0.015). They also had significantly higher bilirubin levels and liver enzymes (p < 0.001), and more postoperative complications including prolonged ICU stay (59% vs. 30%), mechanical ventilation >24h (41% vs. 13%), and renal support (16% vs. 5%). Logistic regression identified diabetes, prolonged bypass time, low ejection fraction, and inotropic use as significant predictors. Conclusion: Postoperative hyperbilirubinemia remains a prevalent complication following cardiac surgery and is significantly associated with adverse clinical parameters. Early identification and risk-based stratification may help mitigate morbidity in affected patients.